RNA-seq and qRT-PCR analyses reveal the physiological response to acute hypoxia and reoxygenation in Epinephelus coioides - Lai, Xingxing; Zhong, Zhongxuan; Lin, Bing; Wu, Yuxin; Ma, Yonghao; Zhang, Cuiping; Yang, Yang; Zhang, Mingqing; Qin, Weijian; Fu, Xiaoqin; Shu, Hu (Frontiers in Physiology, 2022)
Hypoxia is a critical problem in intensive Epinephelus coioides aquaculture systems. In the present study, the physiological responses of E. coioides muscle to acute hypoxic stress (DO=0.6 ± 0.1 mg/L) and reoxygenation (DO=6.0 ± 0.1 mg/L) were analyzed by transcriptome sequencing (RNA-seq) and quantitative real-time PCR (qRT–PCR). RNA-seq was conducted on the muscle tissues of E. coioides in the hypoxia-tolerant (EMS), hypoxia-sensitive (EMW), and normoxic (CM) groups. Among the three groups, a total of 277 differentially expressed genes (DEGs) were identified. KEGG analysis revealed that the pathways significantly enriched after hypoxic stress are involved in the immune response, glycolysis/gluconeogenesis, energy metabolism, vasodilation and proliferation, cell proliferation, and apoptosis. qRT‒PCR verified that the differentially expressed genes FIH-1, PHD-2, PPARα, BCL-XL, LDH-A, and Flt-1 were significantly upregulated after hypoxic stress and returned to normal levels after reoxygenation, suggesting that these DEGs play important roles in responding to hypoxia treatment. In addition, the HIF-1 signaling pathway was also activated under hypoxic stress, and qRT‒PCR confirmed that the expression level of HIF-1α was significantly elevated under acute hypoxic stress, indicating that the HIF-1 signaling pathway is the central pathway in the E. coioides hypoxic response mechanism and activates other related pathways to adapt to hypoxic stress. These pathways jointly regulate energy metabolism, substance synthesis, blood vessel proliferation, cell proliferation, and differentiation and prolong survival time. These results provide ideas for understanding physiological regulation after hypoxic stress and reoxygenation and provide basic insights for the future breeding of hypoxia-tolerant E. coioides.